2022
DOI: 10.37394/23207.2022.19.19
|View full text |Cite
|
Sign up to set email alerts
|

Investments in the Sustainable Development of the Potato Sector in Ukraine Based on the Optimal Balance of Production and Consumption

Abstract: Growing role of potato farming in food security system of the country needs attracting the new investment in preserving and process restructuring of the sector, at scientifically proven approach to defining the optimal scope of potato production, processing, and storage – to avoid the extra stocks, unnecessary losses, and inefficient investment resources at any stage of agri-food chain. Purpose of the study is to justify the conceptual model of investing in development of Ukrainian potato sector, based on calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It is also worth agreeing with the considerations made in the article by Palamarchuk and Mironenko (2019) that when studying the peculiarities of civil service personnel management abroad, it should be borne in mind that they should not be directly copied. In particular, foreign experience should be treated with due regard to their mistakes and national traditions (Palamarchuk & Mironenko, 2019;Lavrov et al, 2022), including the peculiarities of Ukraine's economic life, which is associated with the significant development of agriculture and the need for employees and specialists of the relevant profile (Kozlovskyi et al, 2020;Mudrak et al, 2019). At the same time, the psychology of the national workforce should also be taken into account, as some studies have shown that modern workers may not be ready to accept dramatic changes at the psychological level (Krzywdzinski et al, 2022;Liang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth agreeing with the considerations made in the article by Palamarchuk and Mironenko (2019) that when studying the peculiarities of civil service personnel management abroad, it should be borne in mind that they should not be directly copied. In particular, foreign experience should be treated with due regard to their mistakes and national traditions (Palamarchuk & Mironenko, 2019;Lavrov et al, 2022), including the peculiarities of Ukraine's economic life, which is associated with the significant development of agriculture and the need for employees and specialists of the relevant profile (Kozlovskyi et al, 2020;Mudrak et al, 2019). At the same time, the psychology of the national workforce should also be taken into account, as some studies have shown that modern workers may not be ready to accept dramatic changes at the psychological level (Krzywdzinski et al, 2022;Liang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Legal problems in other countries related to obtaining refugee status became the main object of research in Mavroudi (2023). Modern research also characterizes the direct connection between the country's economic development and migration processes (Dluhopolskyi et al, 2023;Lavrov et al, 2022;Lutsiak et al, 2020). The problems of Asian migrants were also traced by Mohammed (2022), and van Liempt and Staring (2023) focused on the current problems of providing legal protection to refugees from Syria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ukraine is among the top five potato-producing countries globally, has almost half of the country's 1.5 Mha of potato farms with black soils of the forest-steppe zone located in central Ukraine, although the Polesye wetlands of the north harvest the best yields [61][62][63]. Annually, the country harvests approximately 20 Mt, like the USA, and most are grown on a small scale for domestic consumption.…”
Section: Ukrainementioning
confidence: 99%
“…Commercial production land is only about 55 000 ha. In Ukraine, the structure of using the produced potatoes is entirely different; 26%-32% is used for food, 29%-33% for livestock feed, and up to 10% for gross production of non-food items [61]. In 2004, production attained a record of 20.7 Mt, with a yield average of about 13 t ha −1 [63].…”
Section: Ukrainementioning
confidence: 99%